2016
DOI: 10.1128/jvi.02711-15
|View full text |Cite
|
Sign up to set email alerts
|

Signatures in Simian Immunodeficiency Virus SIVsmE660 Envelope gp120 Are Associated with Mucosal Transmission but Not Vaccination Breakthrough in Rhesus Macaques

Abstract: Mucosal surfaces are vulnerable to human immunodeficiency virus (HIV)/simian immunodeficiency virus (SIV) infection IMPORTANCEMost HIV-1 infections occur across a mucosal barrier, and it is therefore important to understand why these sites are vulnerable and how to protect them with a vaccine. To gain insight into these questions, we studied rhesus macaques that were vaccinated with SIVmac239 and unvaccinated controls to determine whether the SIVsmE660 viral variants that infected these two groups were differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 40 publications
2
20
2
Order By: Relevance
“…While these authors found an enrichment in all transmission events for A/K viruses, there was no increase in selection in vaccinated animals. It was suggested that all founder viruses are enriched for the A/K genotype1819. While we also found an enrichment in the A/K genotype compared to the stock, the vaccine effect we report here was a statistically significant increase in the A/K genotype in vaccinated animals compared to sham controls.…”
Section: Discussioncontrasting
confidence: 53%
“…While these authors found an enrichment in all transmission events for A/K viruses, there was no increase in selection in vaccinated animals. It was suggested that all founder viruses are enriched for the A/K genotype1819. While we also found an enrichment in the A/K genotype compared to the stock, the vaccine effect we report here was a statistically significant increase in the A/K genotype in vaccinated animals compared to sham controls.…”
Section: Discussioncontrasting
confidence: 53%
“…Because nucleotide-based dN/dS analyses are problematic when resampling the same population over short periods of time [83], and do not fully reflect the range of diversity that occurs within Env at the amino acid level (conservative vs. non-conservative amino acid changes, insertions and deletions, alterations to glycosylation sites), we developed and implemented a novel approach for statistically quantifying early Env diversity. First, FASTA amino acid alignments of the T/F Envs and early Envs from the same patient were subjected to Sequence Harmony analysis to identify amino acid positions that were significantly different between the two groups of sequences (Z-score ≤ -3) [38,63,84]. As a proof of concept for this approach, we first analyzed sequences from subject R880F, whose early neutralizing antibody responses and escape pathways had been previously mapped in our laboratory in great detail [11].…”
Section: Resultsmentioning
confidence: 99%
“…Single genome analysis of plasma-derived SIV was performed essentially as described previously (Burton et al, 2015; Smith et al, 2016). Additional details can be found in the Supplemental Experimental Procedures.…”
Section: Methodsmentioning
confidence: 99%